Characteristics of Sluggish Cognitive Tempo among adults with ADHD: objective neurocognitive measures align with self-report of executive function - Krone, Beth; Adler, Lenard A.; Anbarasan, Deepti; Leon, Terry; Gallagher, Richard; Patel, Pooja; Faraone, Stephen V.; Newcorn, Jeffrey H. (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction Sluggish Cognitive Tempo (SCT) is a syndrome characterized by cognitive hypo-arousal that often appears as daytime sleepiness or drowsiness, mental fogginess, being easily confused, having difficulty with holding and manipulating information in working memory, and being forgetful. Although it frequently co-travels with attention-deficit/hyperactivity disorder (ADHD) or other conditions and confers significantly greater impairment, there are few studies examining SCT among adults with ADHD. Understanding what features SCT confers in association with ADHD, distinct from other conditions associating with ADHD, is critically important to confirm if SCT is a distinct syndrome that requires special assessment methods and special, distinct treatment efforts to reduce its impact. This study describes the clinical and neuropsychological features of SCT in a sample of adults with well-defined ADHD, and examines the relationship of SCT with other measures of ADHD, neurocognition, executive function (EF), and impairment. Methods A sample of n = 106 adults with ADHD, ages 18-57 years, was assessed for SCT using the Barkley SCT scale. Adults with (SCT+) and without (SCT-) SCT received a comprehensive clinical assessment battery, and neuropsychological testing. Clinical and neuropsychological variables were examined for their associations with SCT. The variables were treated with Principal Axis Factoring with Promax with Kaiser Normalization to elucidate latent constructs and determine performance profiles associated with SCT among people with ADHD. Results EF Deficits and emotional dyscontrol (ED) symptoms significantly differentiated adults with ADHD and SCT whether measured via self or clinician report. Additionally, significantly greater impairment via both clinician and participant report was seen in the SCT + versus SCT - cohorts. SCT was also associated with a significantly distinct profile on the neuropsychological battery, characterized by a pattern of slower latencies and cognitive strategy choices across CANTAB and WAIS subtests, that reveals difficulty with increased cognitive load, which primarily accounted for the higher level of impairment in the SCT group. Discussion The convergence of clinical ratings and neurocognitive measures of EF deficits is consistent with the conclusion that SCT represents a distinct subgroup of adults with ADHD.